2020
DOI: 10.18632/aging.103019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of esophageal-carcinoma cell proliferation by genistein via suppression of JAK1/2-STAT3 and AKT/MDM2/p53 signaling pathways

Abstract: INTRODUCTION Esophageal carcinoma (EsC) is a malignant tumor originating from the mucosal epithelium of the esophagus. In 2015, there were approximately 477,900 new cases of esophageal cancer and 37,500 related deaths in China, accounting for 11.13% and 13.33% of the tumor incidence and mortality, respectively [1]. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…It has also been reported that P53, a famous tumor suppressor gene, inhibits NSCLC cell proliferation, invasion and epithelial‐mesenchymal transition 47–49 . AKT also regulates the tumor characteristics of tumor by MDM2/p53 signal pathway 50–52 . Our results indicated that AKT/MDM2/p53 pathway participates in the protective effect of HAX1 in lung cancer.…”
Section: Discussionsupporting
confidence: 68%
“…It has also been reported that P53, a famous tumor suppressor gene, inhibits NSCLC cell proliferation, invasion and epithelial‐mesenchymal transition 47–49 . AKT also regulates the tumor characteristics of tumor by MDM2/p53 signal pathway 50–52 . Our results indicated that AKT/MDM2/p53 pathway participates in the protective effect of HAX1 in lung cancer.…”
Section: Discussionsupporting
confidence: 68%
“…A total of 261 co-expressed genes of NCAPG were identified by co-expression analysis, and pathway enrichment analysis indicated that these co-expressed genes were significantly enriched in the p53 signaling pathway. Numerous studies have demonstrated that the activation of the p53 signaling pathway is associated with the development of various types of cancer, including breast cancer ( 66 68 ). Furthermore, the association between NCAPG and p53 has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that PL significantly reduced the expression of PI3K/AKT/mTOR at the protein level, therefore, we believe that PL may exert its cycle arrest and induce cell apoptosis through the PI3K/AKT/mTOR signaling pathway. AKT can promote the phosphorylation of MDM2 to inhibit the degradation of p53 [ 44 ], and AKT can directly inhibit the phosphorylation of p21 and p27 to achieve the purpose of cell cycle arrest [ 45 , 46 ]. In addition, AKT inhibits the phosphorylation of GSK-3β [ 47 ], GSK-3β further induced apoptosis [ 48 ], several researchers have revealed that PL shows its cell cycle arrest and apoptosis by inhibiting PI3K/AKT/mTOR in other cell lines [ 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%